Corporations on trial: introducing corporate complicity for international crimes into the ICC to end impunity - Njagi, Cynthia Wambui (Strathmore University, 2020)
Following the mandate of Special Representative John Ruggie’s guidelines on Business and Human rights, urging the need for corporate regulation in international environmental law, questions have arisen on the possibility of corporate accountability in other spheres of law such as international criminal law. Evident concerns such as the effect of the corporate veil on personal jurisdiction and enforcement in international criminal tribunals arise. The corporate veil, gives the entity a separate abstract legal personality, making establishment of criminal responsibility under the current regime difficult due to the assumption of a lack of requisite mensrea. Even so, the individuals making up the corporation can be held criminally liable under international law either individually or when acting as an entity, be prosecuted jointly as a group.
The overall research problem addressed in this study is that despite the Rome Statute’s recognition of group crimes under Article 25(3)(d), little has been done to prosecute groups of persons acting with a common purpose made with the aim of furthering the criminal activity or criminal purpose of the group knowingly and intentionally.19 This has been justified due to the popular opinion that corporates are abstract non-existent entities, however this proposition wrongfully implies that the corporate functions in a vacuum without direction from natural persons with common purpose.